Reactive Oxygen Species Are Involved in Regulating Hypocontractility of Mesenteric Artery to Norepinephrine in Cirrhotic Rats with Portal Hypertension - Chen, Wei (Ivyspring International Publisher, 2014)
Background: Oxidative stress is involved in the hypocontractility of visceral artery to vasoconstrictors and formation of hyperdynamic circulation in cirrhosis with portal hypertension. In the present study, we investigated the effect of reactive oxygen species (ROS) on the mesenteric artery contractility in CCl(4)-induced cirrhotic rats, and the roles of G protein-coupled receptors (GPCRs) desensitization and RhoA /Rho associated coiled-coil forming protein kinase (ROCK) pathways. Methods: The mesenteric artery contraction to norepinephrine (NE) was determined by vessel perfusion system following treatments with apocynin, tempol or PEG-catalase. The protein expression of α1 adrenergic receptor, β-arrestin-2, ROCK-1, moesin and p-moesin was measured by western blot. The interaction between α1 adrenergic receptor and β-arrestin-2 was assessed by co-immunoprecipitation. Results: Pretreatment with apocynin or PEG-catalase in cirrhotic rats, the hydrogen peroxide level in the mesenteric arteriole was significantly decreased, and the dose-response curve of mesenteric arteriole to NE moved to the left with EC(50) decreased. There was no significant change for the expression of α1 adrenergic receptor. However, the protein expression of β-arrestin-2 and its affinity with α1 adrenergic receptor were significantly decreased. The ROCK-1 activity and anti- Y-27632 inhibition in cirrhotic rats increased significantly with the protein expression unchanged. Such effects were not observed in tempol-treated group. Conclusion: The H(2)O(2) decrease in mesenteric artery from rats with cirrhosis resulted in down regulation of the β-arrestin-2 expression and its binding ability with α1 adrenergic receptor, thereby affecting the agonist-induced ROCK activation and improving the contractile response in blood vessels.